Overspeed Detection Using Arduino Uno-based IR Infrared Sensor - Habib Alhaq; Esa Apriaskar; Djuniadi Djuniadi (PTE FTK UIN Ar-Raniry, 2023)
The goal of this project is to measure the speed of an object as it passes through the sensor being utilized. The tool that will be developed as a result of this project has already been designed in software simulation to ensure that it will work as intended. This device uses two infrared sensors as input signals to be processed in accordance with orders.I will be connected to an Arduino Uno through a middle whiteboard as a communication hub between various parts. The parameter used in this tool is the movement of the object going through the infrared sensor because that is what is measured when an object goes through the sensor in this tool. The input data will be processed and then shown on the programmed I2C 16x2 LCD to show the output signal that results from processing the input signal. Making this tool will allow users to minimize unintended incidents and control their speed while driving.